PROMOTION OF HEALTHY LIFESTYLE AND DEVELOPMENT OF VALELOGICAL CULTURE OF PHYSICAL CULTURE SPECIALISTS (Scientific journal of the Fergana State University, 2024)
The purpose of this article is to form a culture of a healthy lifestyle, develop physical qualities, biological, mental, physical conditions and work skills in future physical education teachers, and follow hygienic rules in education.